Maxillomandibular osteotomy healing in a patient with hypophosphatemic rickets. Issue 12 (December 2021) - Ponto, J.; Farkas, D.; Segal, J.D.; Yusupov, Y.
Abstract: Hypophosphatemic rickets is a hereditary disease of childhood that affects bone metabolism. Patients with this disease can have poor bony healing at growth centers due to impaired mineralization of the cartilaginous bone plates. The orthopedic literature has shown appropriate long bone healing in patients with rickets who are undergoing concurrent medical management. However, there has never been a report of successful osteotomy or fracture of the maxillomandibular skeleton in a patient with rickets with documented radiographic and clinical resolution. This report describes a case of successful Le Fort I osteotomy with bilateral mandibular sagittal split osteotomies with concurrent medical management in an 18-year-old female with hypophosphatemic rickets. Before surgery the patient was consented and understood that because there has never been a documented case such as this, she might especially risk complications including non-union, malunion, or unfavorable osteotomy splits. The intraoperative quality of the patient's bone was of normal caliber and allowed routine osteotomy creation and internal fixation with no complications. She was followed for over 3 years and showed uneventful healing. While this disease is especially rare, practitioners should be aware that acceptable healing alongside appropriate medical management has been documented.